Transradial percutaneous coronary intervention for chronic total occlusion of coronary artery disease using sheathless standard guiding catheters. (1st March 2015) - Chen, Huang-Chung; Lee, Wei-Chieh; Hsueh, Shu-Kai; Cheng, Cheng-I; Chen, Chien-Jen; Yang, Cheng-Hsu; Fang, Chih-Yuan; Hang, Chi-Ling; Yip, Hon-Kan; Wu, Chiung-Jen; Fang, Hsiu-Yu
Abstract: Objectives: Our aim was to evaluate the feasibility and safety of routine transradial approach (TRA) percutaneous coronary intervention (PCI) for chronic total occlusion (CTO) lesions using the sheathless technique with standard guiding catheters. Background: Transradial approach PCI was applied for CTO lesions. A major limitation of TRA CTO PCI is the inability to use large guiding catheters because of the relatively small size of the radial artery. Therefore, the sheathless technique for TRA PCI has been recently developed. However, reports on TRA CTO PCI using the sheathless technique are still lacking. Methods: Sixty-eight patients with CTO lesions were enrolled for TRA PCI using the sheathless technique with standard guiding catheters. The baseline characteristics, coronary angiographic characteristics and major procedure or access site related complications were compared between procedure success and procedure failure group to determine the predictors of success in sheathless CTO PCI. In-hospital and 30-day clinical outcomes were also evaluated in this study. Routine assessments of radial artery occlusion via Doppler ultrasound and pulse oximeter were recorded during one-year clinical follow-up. Results: The mean duration of CTO by history was 31.8 ± 42.3 months. The 7 Fr standard guiding catheter was used with the sheathless technique in 91.2%, and bilateral sheathless approach in 42.6% of the study patients. The procedure-related complications included coronary perforation needing covered stent deployment (2.9%), cardiac tamponade (2.9%), collateral perforation needing coil deployment (4.4%), and contrast induced nephropathy (2.9%). Only 2 patients (2.9%) experienced forearm ecchymosis at the radial artery access sites. In-hospital mortality and 30-day all-cause mortality were 2.9%, and 30-day MACEs were 1.5%. The rate of radial artery occlusion during one-year clinical follow-up was only 3.0%. Conclusions: It is feasible and safe to routinely use the sheathless technique with standard guiding catheters for TRA CTO PCI, with a low incidence of procedure-related complications and long-term radial artery occlusion.